Proteostasis disruption and lipid dyshomeostasis in neurodegeneration: exploring common druggable targets across sporadic and monogenic disorders - Pereira Sena, Priscila; Friedrich, Lea; Villarreal, Alcibiades; Fath, Florian; Sopco, Liubovi; Hernández-Guillamon, Mar; Saraiva-Pereira, Maria Luiza; Britton, Gabrielle; Weber, Jonasz Jeremiasz; Schmidt, Thorsten (Frontiers in Molecular Neuroscience, 2025)
Neurodegenerative disorders pose an increasing burden in the aging society. These conditions share several molecular pathomechanisms, some of which may offer opportunities for therapeutic intervention. In this review, we explore a representative selection of sporadic and hereditary neurodegenerative diseases—namely Alzheimer's disease, cerebral amyloid angiopathy, and the polyQ disorders spinocerebellar ataxia types 2 and 3, as well as Huntington's disease—which all feature the accumulation of intra- or extracellular protein deposits as a hallmark. We place particular emphasis on dysregulations in proteostasis—underlying the formation of these aggregates—and the less commonly addressed disturbances in lipid metabolism. By highlighting potential mechanistic links across different classes of neurodegenerative diseases, we aim to provide new insights that may guide the identification of shared druggable targets and the development of broad-spectrum therapeutic strategies.